First Total Syntheses of Novel Non‐Enzymatic Polyunsaturated Fatty Acid Metabolites and Their Identification in Edible Oils. Issue 44 (16th July 2020) - Pavlíčková, Tereza; Bultel‐Poncé, Valérie; Guy, Alexandre; Rocher, Amandine; Reversat, Guillaume; Vigor, Claire; Durand, Thierry; Galano, Jean‐Marie; Jahn, Ullrich; Oger, Camille
Abstract: Oxidative stress (OS) is an in vivo process leading to free radical overproduction, which triggers polyunsaturated fatty acid (PUFA) peroxidation resulting in the formation of racemic non‐enzymatic oxygenated metabolites. As potential biomarkers of OS, their in vivo quantification is of great interest. However, since a large number of isomeric metabolites is formed in parallel, their quantification remains difficult without primary standards. Three new PUFA‐metabolites, namely 18‐F3t ‐isoprostane (IsoP) from eicosapentaenoic acid (EPA), 20‐F4t ‐neuroprostane (NeuroP) from docosahexaenoic acid (DHA) and 20‐F3t ‐NeuroP from docosapentaenoic acid (DPAn‐3 ) were synthesized by two complementary synthetic strategies. The first one relied on a racemic approach to 18( RS )‐18‐F3t ‐IsoP using an oxidative radical anion cyclization as a key step, whereas the second used an enzymatic deracemization of a bicyclo[3.3.0]octene intermediate obtained from cyclooctadiene to pursue an asymmetric synthesis. The synthesized metabolites were applied in targeted lipidomics to prove lipid peroxidation in edible oils of commercial nutraceuticals. Abstract : Lipid peroxidation in marine oil‐based omega‐3 food supplements? The first total syntheses of three new lipid peroxidation metabolites and their positive identification in edible oils thanks to targeted lipidomics are reported. These results provide a valuable tool to evaluate lipid peroxidation and raise the question whether and how these oxidized lipid metabolites contribute to the effects of these nutraceuticals.